Wireless charging technology and the future of electric transportation - Sŏ, In-su; Cho, Dong-Ho; Franke, Jorg; Hong, Soon-Man; Lee, Byung Song; Miller, John M., 1949-; Risch, Florian; Shinohara, Naoki, 1968-; Turki, Faical (Society of Automotive Engineers. Electronic publications, 2015)
This book brings an in-depth analysis of the most important areas of interest in this new area, such as: Working principles of wireless power transfer technology; Current technology and its projected future impact on electric vehicles; Comparison between conductive and wireless charging of electric vehicles; Introduction to dynamic wireless charging systems; Technological challenges and international technical standards activities; Applications in consumer electronics, rail, aviation, marine, and off-road transportation; Long-distance electrical energy transfer .